2017
DOI: 10.1016/j.ekir.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training in Elderly People Undergoing Hemodialysis: A Systematic Review and Meta-analysis

Abstract: IntroductionPrevious reviews have indicated the effectiveness of exercise in people undergoing hemodialysis. However, these analyses did not take into account whether the subjects were elderly. We performed a systematic review of the effects of exercise training in elderly people undergoing hemodialysis and updated the evidence of exercise for people undergoing hemodialysis by adding recent research data.MethodsWe searched 8 electronic databases up to June 2016. Inclusion criteria were as follows: randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 68 publications
7
63
0
2
Order By: Relevance
“…Once the full text of those articles was screened, 25 RCTs (1.8% of those identified by the search process) met all inclusion criteria . We also included five systematic reviews for our review of generic HRQOL …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the full text of those articles was screened, 25 RCTs (1.8% of those identified by the search process) met all inclusion criteria . We also included five systematic reviews for our review of generic HRQOL …”
Section: Resultsmentioning
confidence: 99%
“…Another meta‐analysis of RCTs implementing intradialytic exercise demonstrated a significant improvement in physical subcomponents (SMD 0.3 95% CI 0.04‐0.55) of generic HRQOL questionnaires but no significant difference in the mental component . Similarly, a meta‐analysis of any exercise in individuals on HD demonstrated a significant improvement in physical component summary score of the SF36/KDQOL (SMD 0.53 (95% CI, 0.52‐0.82) . However, this improvement was not seen in elderly HD patients (only one study included).…”
Section: Resultsmentioning
confidence: 99%
“…Frailty among hemodialysis patients is primary characterized by physical inactivity and poor physical performance. A comprehensive meta-analysis showed that physical exercise interventions improved physical function, including muscle strength and aerobic capacity, in hemodialysis patients [14,16]. Furthermore, wearing a pedometer, setting activity goals, use of a step diary (self-monitoring), and feedback from medical staff were shown to increase physical activity by providing motivation, reaching approximately 1000 steps per day, in hemodialysis patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more than 70% of elderly patients treated with chronic hemodialysis are classified as frail [7,8]. Although physical inactivity and decreased physical function in hemodialysis patients are associated with adverse outcomes, including mortality and hospitalization, [9][10][11][12][13] these are potentially modifiable conditions [14][15][16]. Early identification and interventions for conditions of frailty are essential to implement effective disease management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of physical activity has been directly linked to numerous negative health concerns such as: Obesity, High blood pressure, Lower quality of life, Musculoskeletal problems, such as low back pain and muscle tightness [13,14,15].…”
Section: Introductionmentioning
confidence: 99%